2016
DOI: 10.3732/ajb.1600166
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional anatomical effects in a mistletoe–host relationship: Psittacanthus schiedeanus mistletoe and its hosts Liquidambar styraciflua and Quercus germana

Abstract: The bidirectional effects between the parasite and its hosts comprise modifications in secondary phloem that are potentially affected by the phenology of its hosts, a combination of hormonal agents such as auxins, and the symplasmic or apoplasmic pathway for solutes import.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 56 publications
0
14
0
3
Order By: Relevance
“…Also, host specificity may be scale dependent, which can explain the apparently contradictory results on the importance of host preferences to genetic differentiation in Phoradendron californicum at different spatial scales (Lira‐Noriega et al ., ; Yule et al ., ). In the present case, scale‐dependent host preferences would explain why Liquidambar (Altingiaceae) appears to be the main host for P. schiedeanus in central Veracruz (López de Buen & Ornelas, ; Kuijt, ; Cocoletzi et al ., ), but is less frequently (or not) infected throughout the rest of its distribution range (Fig. S2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, host specificity may be scale dependent, which can explain the apparently contradictory results on the importance of host preferences to genetic differentiation in Phoradendron californicum at different spatial scales (Lira‐Noriega et al ., ; Yule et al ., ). In the present case, scale‐dependent host preferences would explain why Liquidambar (Altingiaceae) appears to be the main host for P. schiedeanus in central Veracruz (López de Buen & Ornelas, ; Kuijt, ; Cocoletzi et al ., ), but is less frequently (or not) infected throughout the rest of its distribution range (Fig. S2).…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive host-race formation has been proposed as a main mechanism of population divergence for parasites in general (de Vienne et al, 2013;Hoberg & Brooks, 2015), and for mistletoes in particular (Norton & Carpenter, 1998;L opez de Buen & Ornelas, 2002;Lara et al, 2009;Ram ırez & Ornelas, 2012). For example, differential survival of P. schiedeanus on different host trees has been attributed to host compatibility (L opez de Buen & Ornelas, 2002;Cocoletzi et al, 2016). L opez de Buen & Ornelas (2002) observed that the parasite's seedling establishment and survival did not vary among different host species, and that differences in survival were only evident during later developmental stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Es uno de los géneros más grandes de la familia Loranthaceae. Consta de 119-120 especies (Kuijt, 2009a;Cocoletzi et al, 2016), distribuidas a lo largo del Nuevo Mundo, alcanza su límite norte en la parte central de Baja California (México), con una representación menor en el Caribe (Jamaica y algunas de las Antillas Menores) y numerosas especies en elevaciones bajas y medias en Sudamérica (Bolivia y norte de Argentina).…”
Section: Introductionunclassified
“…Nicaragua represents a gap in its distribution and the Northern and Southern populations show some morphological differentiation (Kuijt 2009). The species parasitizes over 20 different hosts Cocoletzi, Angeles, Ceccantini, Patrón, & Ornelas, 2016) and it is considered part of a species complex involving P. calyculatus (DC.) G. Don, P. breedlovii Kuijt, and P. angustifolius Kuijt (Diaz-Infante, Lara, del Coro Arizmendi, Eguiarte, & Ornelas, 2016;Pérez-Crespo et al, 2017).…”
mentioning
confidence: 99%